2011
DOI: 10.1371/journal.pone.0019987
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Processing of Swallowing in ALS Patients with Progressive Dysphagia – A Magnetoencephalographic Study

Abstract: Amyotrophic lateral sclerosis (ALS) is a rare disease causing degeneration of the upper and lower motor neuron. Involvement of the bulbar motor neurons often results in fast progressive dysphagia. While cortical compensation of dysphagia has been previously shown in stroke patients, this topic has not been addressed in patients suffering from ALS. In the present study, we investigated cortical activation during deglutition in two groups of ALS patients with either moderate or severe dysphagia. Whole-head MEG w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
49
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 47 publications
4
49
2
1
Order By: Relevance
“…It has been reported that the oropharyngeal transit time of ALS patients is longer than that of healthy subjects (Cha, 1989;Kawai et al, 2003;Higo et al, 2004;Teismann et al, 2011;Ruoppolo et al, 2013). In this study, in contrast to the VF temporal analysis, tongue thickness was found to be associated with the oral preparatory and transit time but not with the pharyngeal transit time, independent of the bulbar-related subscores.…”
Section: Discussioncontrasting
confidence: 79%
“…It has been reported that the oropharyngeal transit time of ALS patients is longer than that of healthy subjects (Cha, 1989;Kawai et al, 2003;Higo et al, 2004;Teismann et al, 2011;Ruoppolo et al, 2013). In this study, in contrast to the VF temporal analysis, tongue thickness was found to be associated with the oral preparatory and transit time but not with the pharyngeal transit time, independent of the bulbar-related subscores.…”
Section: Discussioncontrasting
confidence: 79%
“…Still, the majority of studies reporting swallowing physiology/function present observations in descriptive terms, limiting our ability to compare results across studies or measure discrete degrees of change. For example, hyolaryngeal excursion is often reported as “reduced” (e.g., [33,45,60]), however, when measured in reference to a scalar or anatomical marker, the results are more variable (e.g., [51,65]). Quantification of swallowing physiology has largely been limited to studies using manometry (e.g., [40,59,66]) and EMG (e.g., [67,68]).…”
Section: Discussionmentioning
confidence: 99%
“…For artifact correction, each individual's coregistered EMG signal was used to identify swallowing acts as previously published [18][19][20]. Stimulation episodes contaminated by swallows were rejected.…”
Section: Meg Data Analysismentioning
confidence: 99%
“…Stimulation episodes contaminated by swallows were rejected. By applying a fourth order two-pass Butterworth filter prior to further computations, MEG data were filtered within five different frequency bands: theta (4-8 Hz), alpha (8-13 Hz), beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), low gamma (30-60 Hz), and high-gamma (60-80 Hz).…”
Section: Meg Data Analysismentioning
confidence: 99%